El fomento de las sociedades cooperativas - Díaz de la Rosa, Angélica (Revista de Derecho, 2019)
Multiples international character rules and within Spain and also peruvian a force the increase of by cooperative societies. To be able to enforce this law we have to take into account that these purpose cannot be achieved with an absurd multiplication of regional cooperative laws –like has happened in the spanish case- that can even affect the principles of the market union. The case is we have to divulge the laws and apply socioeconomics politics that help favour this cooperation, and, also, that favour these enfornt of other social formulas. If these measure of promotion that benefit both the cooperative sector and other forms organization, these equality ends in redundancy and harms these cooperatives, being treated equally when their condition are different.
Keywords: Cooperative company; promotion of cooperatives; adequate legislation